한반도 동해안 석호의 관속식물상 - 김중현; Jung-hyun Kim; 김선유; Sun-yu Kim; 홍정기; Jeong-ki Hong; 남기흠; Gi-heum Nam; 안지홍; Ji-hong An; 이병윤; Byoung Yoon Lee; et al. (Sigmul bunryu hag-hoeji = Korean journal of plant taxonomy, 2017)
동해안 석호는 해수와 담수가 섞인 독특한 형태의 기수호이며, 수변식생이 발달되어 생물다양성이 풍부한 지역이다. 본 연구는 국내에 분포하는 17개소의 석호에 대한 식물상과 식물 종조성 등의 조사를 통하여 석호 식생에 대한 안정적인 보전계획 수립을 위한 기초자료를 제시하고자 한다. 17개소의 석호에 대한 식물상 조사결과, 관속식물은 118과 378속 655종 13아종 46변종 6교잡종, 총 720분류군이 확인되었다. 이중에서 한반도 고유종이 11분류군, 멸종우려 식물이 18분류군, 식물구계학적 특정식물인 IV-V등급 식물이 23분류군이었다. 남방계식물은 4분류군, 북방계식물은 8분류군으로 조사되었고, 특히 남한 내 희귀식물인 갯활량나물(Thermopsis lupinoides), 기름당귀(Ligusticum hultenii), 벼룩아재비(Mitrasacme alsinoides), 통발(Utriculariaaustralis), 검정납작골풀(Juncus fauriei), 새방울사초(Carex vesicaria), 천도미꾸리광이(Puccinellia kurilensis)등이 동해안 석호에서 생육하고 있었다. 외래식물은 96분류군이 발견되었다. 한반도 석호는 식물다양성이 풍부하고, 희귀식물 및 식물지리학적 중요한 식물이 관찰된다. 석호의 효과적인 관리와 생물다양성 보전을 위해 체계적인 사항들이 논의되었다. Eastern coastal lagoons are a particular type of estuarine systems where seawater mixes with fresh water from their catchments. With the development of aquatic vegetation, this area shows high level of biodiversity. The purpose of this study is to produce a strategy for the comprehensive conservation of the vegetation of coastal lagoons through studies of the floristics and plant species compositions in 17 eastern coastal lagoons in Korea. Vascular plants were collected 109 times, from June of 2010 to November of 2014. The results showed that there were 720 taxa in total, including 118 families, 378 genera, 655 species, 13 subspecies, 46 varieties, and 6 hybrids. Korean endemic species numbered 11 taxa, and vascular plants listed in the red list according to the International Union for Conservation of Nature (IUCN) numbered 18 taxa. Indicator species of fourth (IV) and fifth (V) degree, as specified by floristic subregions, numbered 23 taxa. Among the species investigated in this survey, there were 4 taxa of plants of southern origin and 8 taxa of plants of northern originin the Korean peninsula. Several rare plants, Thermopsis lupinoides, Ligusticum hultenii, Mitrasacme alsinoides, Utricularia australis, Juncus fauriei, Carex vesicaria, and Puccinellia kurilensis, were distributed in eastern coastal lagoons. In all, 96 alien plants were recorded in the investigated area. The coastal lagoons on the eastern coast of Korea showed high plant diversity with many rare plants and phytogeographically important plants. Conservation strategies to ensure biodiversity and effective management of coastal lagoons are discussed in detail.